The New Paradigm On The Islamization Of Science: Islam As Knowledge And Belief - Prima Aswirna; Reza Fahmi (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2016)
The research based on fact about more than ten years experience theexisting of Islamic Psychology Department at State Institute of Islamic StudiesImam Bonjol Padang. During the implementation of the integration on Islamand science (Psychology), The research used quantitative method as aperspective. Then I explored the problems on the capture of academic profileinstitution. The populations on the research were a lecturer who was teaching inthe Islamic Psychology Dept. and students (about 35 people/ lecturer and 145pupils). The sample was about 32 lecturers and 107 students. The measurementof size of respondents based on Slovin formula: N/1+N.e2. The data collectedby psychological scale, observation and documentation. The regression has beenused to analyze data